2017
DOI: 10.1007/s10792-017-0615-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in contact lens fitting parameters following cross-linking in keratoconus patients of Indian ethnicity

Abstract: Despite no statistically significant change in objective parameters of lens fit, a tendency for flatter lens fit along with contact lens induced further flattening of the ectatic cornea which resulted in marked improvement in both objective and subjective contact lens fit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…in their study. [18] Although the corneal sensations are reduced following CXL as reported in the literature, one patient developed CL intolerance in this study. [23]…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…in their study. [18] Although the corneal sensations are reduced following CXL as reported in the literature, one patient developed CL intolerance in this study. [23]…”
Section: Discussionmentioning
confidence: 52%
“…who have shown reduction in spherical and cylinder values in their study. [18] However, the mean postrefraction CL power is higher – this may be due to the steeper base curve post-CXL compared to preoperative base curve. The daily mean awake wearing time in this study was 10.36 h as against 8 h/day as reported by Singh et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study also found that CXL surgery did not increase compliance with RGPCL wear. Previous studies have shown that RGPCL wear post-CXL was relatively well tolerated due to the decreased corneal sensitivity and the flattening effect of CXL [11,20,21]. Unlu et al [11] also found that the mean duration of RGPCL wear increased after CXL surgery.…”
Section: Discussionmentioning
confidence: 98%